Cryptocurrency Crime Risks Modeling: Environment, E-Commerce, and Cybersecurity Issue - Olha Kovalchuk; Ruslan Shevchuk; Serhiy Banakh (IEEE Access, 2024)
Digital trends like blockchain have led to cryptocurrency payments becoming popular in e-commerce. While cryptocurrencies have benefited users, they have also attracted criminals who use them to commit cyberattacks and harm security. In this research paper, we present an analysis of the following factors that can strongly influence the development of the cryptocurrency environment and be associated with cryptocurrency-related crime at the national level: GDP, digital development, e-commerce market size, the level of mass adoption of cryptocurrency, the level of national cybersecurity, and fraud in cryptocurrency crime for selected countries worldwide. By applying correspondence analysis, we constructed visually intuitive models based on assessments from the global data and business intelligence platform and official statistical reports. We have established a fairly strong positive correlation between fraud in cryptocurrency crime and digital development, e-commerce market size, and the level of mass adoption of cryptocurrency; a fairly strong negative correlation between the level of fraud in cryptocurrency crime and the level of cybersecurity in a specific country; a fairly strong positive correlation between the level of mass adoption of cryptocurrency and the level of cybersecurity. The proposed models give decision-makers a clear understanding of the key factors in cryptocurrency that pose a high risk of related crime.